2021
DOI: 10.1080/10826076.2020.1866600
|View full text |Cite
|
Sign up to set email alerts
|

Scanning densitometry and mass spectrometry for HPTLC analysis of lipids: The last 10 years

Abstract: This work is a review on HPTLC contribuon to lipid analysis in complex matrices, in the period from 2010 to now, lapse of me where hyphenaon with other techniques, especially Mass Spectrometry, has experienced an important growth.Scanning densitometry (SD)-UV/FL of separated lipids, as the core of detecon and centerpiece for hyphenaon, and its coupling with MS using so ionizaon techniques (ESI, APCI, MALDI, DESI and others), are the central axis of this work. The occasional intercalaon in this coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 136 publications
0
18
0
Order By: Relevance
“…TLC/MALDI enables the analysis of complex organic mixtures [253,254]. Previous reports indicate that this approach is effective in the identification of active compounds of plant origin, such as lipids or flavonoids [255,256]. The use of "direct analysis in real-time" (DART) in conjunction with TLC also seems to be an interesting approach.…”
Section: Gas Chromatography (Gc)mentioning
confidence: 99%
“…TLC/MALDI enables the analysis of complex organic mixtures [253,254]. Previous reports indicate that this approach is effective in the identification of active compounds of plant origin, such as lipids or flavonoids [255,256]. The use of "direct analysis in real-time" (DART) in conjunction with TLC also seems to be an interesting approach.…”
Section: Gas Chromatography (Gc)mentioning
confidence: 99%
“…One of the areas of interest in current analytical chemistry is lipid analysis. Cebolla et al (2021) have recently presented a review on HPTLC contribution to lipid analysis in complex matrices during the period 2010-2021, when hyphenation of TLC to MS methods had experienced significant growth. Authors demonstrated that HPTLC separation of lipids on classes allowed the subsequent analysis by MALDI-TOF, resolving the difficulties in the analysis of acidic glycerophospholipid species due to ion suppression by phosphatidylcholine species.…”
Section: Applicationsmentioning
confidence: 99%
“…The plates further contain thinner layers and the surface is smoother [ 55 ]. These features altogether reduce sample quantity requirements and allow for more economical and faster separation with reduced diffusion rates [ 55 57 ]. This results in higher sensitivity, more efficient separation and better sample resolution, and also positively affects reproducibility [ 55 57 ].…”
Section: Introductionmentioning
confidence: 99%